Systematization of the practice of a model for the training of students in Orientation - Jiménez Espinoza, Ericka (2022)
This article presents the systematization of the supervised experience of a group of students of the Professional Practice II course of the Counseling career of the University of Costa Rica.  In the application of a theoretical- practical training model for students, during the implementation of the personal-group modality, with children.  For data collection, an evaluation guide was used to estimate the students during the development of the orientation sessions.  To achieve this objective, the systematization model proposed by Oscar Jara was used. This was done to strengthen the training and professional development of the trainees. The aim is to report the successes and failures of this training to improve both the course and the professional practice, and to disseminate the results obtained. One of the most important points of arrival of the data obtained is that, in general, there was a good performance on the part of the trainees, because significant contributions are highlighted in this period of the training. However, there are also aspects to be corrected in which both the students and the teachers have stated that they need to improve their professional competence.